Recent Insights on Prevalence and Corelations of Hypoactive Delirium - Vaios Peritogiannis; Maria Bolosi; Charalampos Lixouriotis; Dimitrios V. Rizos (Behavioural Neurology)
Delirium is a complex neuropsychiatric syndrome which is common in all medical settings. It often goes unrecognized due to difficulties in the detection of its hypoactive variant. This review aims to provide an up-to-date account on recent research on hypoactive delirium (HD). Thirty-eight studies, which were conducted in various clinical settings, including the Intensive Care Unit (ICU), were included in this review. Those studies involved recent research that has been published during the last 6 years. Prevalence of HD was found to vary considerably among different settings. HD seems to be more common in critically ill patients and less common in patients examined by consultation-liaison psychiatric services and in mixed patient populations. The presence of HD in ICU patients was associated with higher short- and long-term mortality and other adverse outcomes, but no such association was reported in other settings. Research on other possible associations of HD with clinical variables and on symptom presentation yielded inconclusive results, although there is some evidence for a possible association of HD with benzodiazepine use. There are several methodological issues that need to be addressed by future research. Future studies should examine HD in the primary care setting; treatment interventions should also be the objective of future research.